2016
DOI: 10.1155/2016/7407919
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Treatment for Lupus Nephritis: Long-Term Results in 178 Patients

Abstract: Lupus nephritis is one of the most severe Systemic Lupus Erythematosus features, defining treatment modality and prognosis. Our retrospective study, including 178 patients treated for lupus nephritis during 23 years with mostly cyclophosphamide-based initial regimens followed by azathioprine or mycophenolic acid, demonstrates 84.8% of renal response with 19.2% of flares, 15-year patient survival 78.7% and kidney survival 76.3%, and low damage accrual. Both patient and kidney survival significantly differ for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The results of this study were consistent with other studies that also identified baseline renal function, 13,14 chronicity index, 29 remission 30,31 and relapse 12 to affect long-term renal survival. The latter may explain why one-tenth of our patients eventually developed progressive CKD, despite high remission rates of nearly 97%.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study were consistent with other studies that also identified baseline renal function, 13,14 chronicity index, 29 remission 30,31 and relapse 12 to affect long-term renal survival. The latter may explain why one-tenth of our patients eventually developed progressive CKD, despite high remission rates of nearly 97%.…”
Section: Discussionsupporting
confidence: 92%
“…17,19-26 However, only a few studies have looked at the value of partial remission with regard to long-term outcomes. 17,27,28 We aim in this study to examine the rate of short-term remission (6 months) to standard of care induction treatments, and study its predictors and effect on long-term renal outcomes in Saudi patients with PLN.…”
Section: Introductionmentioning
confidence: 99%